Reflections on being an expert - Debbie Garratt (Grounded Theory Review: An International Journal)
In this essay, the author explores the journey of undertaking a Grounded Theory (GT) research project on a topical area closely aligned with her profession, although on a specific aspect about which little was known. By following the data as directed in GT, the area under study became one in which the researcher was more of an expert. How this shift from “little known” to “expert area” occurred and the challenges relative to overcoming the researcher’s anxiety associated with this shift are two themes explored. The researcher’s conclusion is that expert knowledge enabled nuances to be seen that may otherwise have been missed, but that having expert knowledge necessitated greater attention to ensuring sensitisation, not preconception.